CLINICAL AND EPIDEMIOLOGICAL ANALYSIS ON SYPHILIS AMONG MEN WHO HAVE SEX WITH MEN - Hristina Haidudova; Klimentina Gospodinova; Milena Karcheva; Dimitar Gospodinov (Peytchinski Publishing, 2024)
Purpose of the study: To investigate demographics, prevalence, risk factors and the different clinical forms and symptoms of syphilis in men who have sex with men (MSM). Material/Methods: 50 MSM with syphilis were registered at the Clinic of Dermatology and Venereology in the city of Pleven, Bulgaria, for the period 2008-2022. The diagnosis was confirmed by serological tests. Patients were distributed by their socio-demographic status. Risk factors and sexual behavior were studied, as well as clinical symptoms and co-morbidities of syphilis. Results: Of 50 MSM patients the most affected is the age between 20-29 years (54%). 34% of them are university graduates, 88% abused alcohol, nicotine and drugs in combination, 70% had sexual contacts with a casual partner, 26% of them had HIV co-infection. Secondary and early latent syphilis are the most common clinical forms of the disease (34%). The typical symptoms of primary and secondary syphilis were clinically manifested, 34% of them are localized in the genital. There is a significant correlation of the clinical form with the localization of the skin-mucosal lesions (p < 0.001). Antibiotic therapy is effective and leads to negative serological test results by the end of the second year of treatment. Conclusions: For 15 years (2008-2022), the number of registered MSM with syphilis in the Clinic of Dermatology and Venereology in Pleven increased after 2016 especialy in the time of the COVID-19 pandemic. Our results are close to the published data on the problem in the scientific literature for the last 10 years.